Hasil Belajar IPS para Siswa dan Siswi Kelas 6 SD pada Beberapa Tipe Pembelajaran - Edy Budianto; Corebima Aloysius, Duran; Ika Rahayunita, Cicilia (Jurnal Penelitian dan Pendidikan IPS, 2024)
In learning, the type of learning has an important role in the learning process and outcomes. The application of this type of learning in a learning process will certainly influence the learning outcomes of male and female students. The aim of this research is to determine the social studies learning outcomes of 6th grade elementary school male and female students in several types of learning. This research approach uses a quantitative, quasi-experimental method with a pretest post-test only control group design. The sample for this research used 4 groups of 6th grade students totaling 100 students at SDN Kesatrian 1 for the 2022-2023 KD academic year. IPS 3.2 curriculum 2013 with 25 students in each class, class 6B as an experimental class with an inquiry model and video media, class 6D as a positive control A with an inquiry model, class 6C as a positive control B with video media, and class 6A as a conventional control . This research instrument is in the form of a pretest question sheet and learning outcomes of 20 multiple choice questions which are arranged based on the bloom dimensions which have gone through validity, realibiity, different tests, and been validated by validators who are experts in the field. Based on the results of the double Anakova hypothesis test, the results of this study state that there are differences in learning outcomes based on the type of learning applied in each class. However, the results of further tests stated that there were no differences in social studies learning outcomes for male and female students in several types of learning.